Velayatul Faqih and the Resurgence of Islamic Movements Worldwide - Ibrahimian, Hojjatollah (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The Islamic Revolution for the people of Iran has become an essential necessity. Therefore, this paper aims to examine how the awakening of the Islamic world and the most significant challenges faced by the Islamic Revolution of Iran from its inception to the present day, under a government based on the principle of the Guardianship of the Jurist, often confronted with Western propaganda conflicting with Islamic values. Despite facing various obstacles and limited resources, the Government of the Islamic Revolution of Iran has made significant strides, even transforming its military forces into one of the strongest in the world and balancing conventional forces long dominated by the United States and its allies.